Effects of a secondary prevention combination therapy with an aspirin, an ACE inhibitor and a statin on 1-year mortality of patients with acute myocardial infarction treated with a beta-blocker. Support for a polypill approach - Zeymer, Uwe; Jünger, Claus Heinrich; Zahn, Ralf; Bauer, Timm; Bestehorn, Kurt; Senges, Jochen; Gitt, Anselm Kai (Current medical research and opinion, 2011)
Objective: Large randomized clinical trials have shown the efficacy of aspirin, ACE (angiotensin converting enzyme) inhibitors and statins as secondary prevention measures in patients after an acute coronary syndrome with and without ST elevations. Therefore we aimed to determine the effect of a combination therapy with these three drugs on 1-year mortality after acute myocardial infarction (AMI). Methods: We prospectively followed 9998 survivors of acute myocardial infarction treated with a beta-blocker for 1 year. Patients were divided into three groups according to their therapy with aspirin, ACE inhibitors and statins: 3 drugs, 2 drugs or 0-1 drug. Results: The majority of patients (n = 6260, 62.6%) were treated with 3 drugs, 2986 (29.9%) with 2 drugs and 752 (7.5%) with 0-1 drug. In the univariate analysis 1-year mortality was 4.9%, 9.7% and 13.6%, respectively. After adjusting for confounding factors in the propensity score analysis the odds ratios for 1-year mortality were significantly increased with 0-1 drug (odds ratio 1.67, 95% CI 1.24-2.27) and with 2 drugs (odds ratio 1.54, 95% CI 1.26-1.87) in comparison with the group treated with all 3 drugs. However, in the ACOS registry the treatment was left to the discretion of the physician. This could lead to a selection bias, which cannot be fully eliminated by using multiple regression analysis. Conclusions: A combination therapy with aspirin, an ACE inhibitor and a statin reduces 1-year mortality in patients after AMI. Therefore a polypill approach with these three agents should be considered to increase drug compliance and reduce mortality after acute myocardial infarction.
Gesehen am 16.01.2023